Complete clinical remission of invasive Candida infection with CARD9 deficiency after G-CSF treatment. (June 2020) - Du, Bailu; Shen, Nan; Hu, Jinfeng; Tao, Yue; Mo, Xi; Cao, Qing
Highlights: CARD9 deficiency is an autosomal-recessive primary immunodeficiency characterized by susceptibility to recurrent Candida infections. A homozygous mutation in CARD9 (c.819-820insG) was identified. The combination of G-CSF and antifungal agents was suitable for Children cases with CARD9 immunodeficiency. Abstract: Caspase-associated recruitment domain-containing protein 9 (CARD9) deficiency is an autosomal-recessive primary immunodeficiency characterized by susceptibility to recurrent Candida infections, and its diagnosis and treatment is challenging. The present study aims to investigate the genetic characteristic and treatment strategy of a Chinese pediatric patient with CARD9 deficiency. In the present study, whole-exome sequencing (WES) was performed to screen the causal variants in a Chinese pediatric patient who exhibited an invasive Candida infection in the abdominal cavity and central nervous system. After the disease-causing gene being confirmed, the patient was treated with a combination of G-CSF and antifungal agents. DNA sequencing revealed a homozygous insertion mutation (c.819–820insG) in exon 6 of the CARD9 gene, which led to downstream amino acids conversion on codon 274 (p.D274fsX60). Th17 cell populations and cytokine levels showed decreased levels. The treatment regimen successfully resolved the patient's symptoms, and he remained symptom-free after more than 1 year of follow-up. This study described an invasive Candida infection in a pediatric patient and WES identified an insertion variant of the CARD9 gene. A combination of G-CSF and antifungal agents was highly effective in treating the invasive fungal infection accompanied by CARD9-induced immunodeficiency.